Pertumbuhan Rhizophora apiculata pada Sistem Silvofishery di Desa Simpang Tiga Jaya Kecamatan Tulung Selapan Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Rahmad, Beni; Lensari, Delfy; Wulandari, Riska; Harefa, Ribka (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the growth of Rhizophora apiculata in the silvofishery system in Simpang Tiga Jaya Village, Tulung Selapan District, Ogan Komering Ilir Regency, South Sumatra Province. The research was conducted to compare the effects of two planting locations—pond and riparian areas—and two types of seed sources, namely propagules and natural wildings, on the growth and survival rate of Rhizophora apiculata. A quantitative experimental method was used, with observations conducted over 4 month on variables such as plant height, stem diameter, number of leaves, root length, and root weight. The results showed that seedlings originating from propagules exhibited higher growth rates and survival percentages compared to wilding seedlings. The highest survival rate was observed in treatment M2S2 (riparian location + propagules) at 76.67%, followed by M1S2 (pond location + propagules) at 72.22%. Soil analysis revealed that the pond location had higher nutrient content, thus supporting more optimal plant growth. Overall, the source of seedlings was identified as the main factor contributing to the successful rehabilitation of Rhizophora apiculata within the silvofishery system.